Comparative study of laproscopic versus open appendicectomy - Patil, Mahadeo R.; Patil, Sandhyarani M. (International Surgery Journal, 2016)
Background:Open appendicectomy (OA) has been the treatment of choice for acute appendicitis since its introduction in 1884. Since its initial description in 1983, laproscopic appendicectomy (LA) has struggled to prove its superiority over the open technique. This is in contrast to laproscopic cholecystectomy over open cholecystectomy. Some early studies showed equivocal results about benefits of LA. Recent studies showed overall benefits in favour of LA. So we have done comparative study with the aim to compare the safety and benefits of LA over OA. Methods: We have studied data of 753 appendicectomies done in Dr. D.Y. Patil Medical College Kolhapur from July 2011 to June 2016 for a period of 5 years. Results:We found mean operation time 32±5.7 minute and 36±7.4 minute in LA and OA. Duration of postoperative stay was 1.2 days shorter in LA group. LA required 1.1 less shots of analgesics. Oral feeding was resumed 21 hours earlier in LA as compared to OA. Conclusions:Our study found that LA is effective and safe procedure irrespective of age, sex and BMI of the patient. It requires less operative time, has minimal complications, less hospital stay, less narcotic analgesics requirements, early return of bowel movement and the advantage of diagnosing the concomitant pathologies.